2017
DOI: 10.1186/s12936-017-1856-2
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a laboratory quality assurance pilot programme for malaria diagnostics in low-transmission areas of Kenya, 2013

Abstract: BackgroundOne objective of the Kenya National Malaria Strategy 2009–2017 is scaling access to prompt diagnosis and effective treatment. In 2013, a quality assurance (QA) pilot was implemented to improve accuracy of malaria diagnostics at selected health facilities in low-transmission counties of Kenya. Trends in malaria diagnostic and QA indicator performance during the pilot are described.MethodsFrom June to December 2013, 28 QA officers provided on-the-job training and mentoring for malaria microscopy, malar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0
2

Year Published

2017
2017
2019
2019

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 12 publications
0
19
0
2
Order By: Relevance
“…Another important limitation was that slide preparation quality, including the stain type and adequacy, was not evaluated. Although both NMCP and WHO recommend Giemsa preferentially for malaria microscopy, the use of both Giemsa and Field stains was common in health facilities [ 8 , 10 , 16 ]. Slides were not matched on parasite density either.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Another important limitation was that slide preparation quality, including the stain type and adequacy, was not evaluated. Although both NMCP and WHO recommend Giemsa preferentially for malaria microscopy, the use of both Giemsa and Field stains was common in health facilities [ 8 , 10 , 16 ]. Slides were not matched on parasite density either.…”
Section: Discussionmentioning
confidence: 99%
“…Twenty-one facilities were part of the pilot QA programme from June to December 2013; these facilities were randomly selected from among 45 public-sector pilot QA programme facilities across 4 service-provision levels (i.e., dispensary, health centre, primary hospital, secondary hospital). The pilot QA programme was implemented in 83 health facilities (45 [54%] public-sector and 38 [46%] private-sector); facilities were selected to participate based on capacity to perform malaria microscopy and distance from the QA officers’ primary duty stations [ 16 ]. These facilities are referred to as ‘QA-pilot facilities.’ Twenty-one public health facilities of the same service-provision level and located in the same county as the QA-pilot facilities, but which did not participate in the QA-pilot programme, were also randomly selected to participate in the survey.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous research has demonstrated the effectiveness of malaria microscopy refresher training on improving technician performance, 13,[31][32][33][34][35][36][37] although some studies have not been able to corroborate this effect. [38][39][40][41] This study adds to the evidence base for malaria microscopy assessments by broadening the scale of outcome measures related to the intervention in exploring both slide-and person-level results. The primary outcome evaluates the competence of participating laboratory technicians through assessment of three major malaria microscopy diagnosis areas (i.e., parasite detection, species identification, and parasite quantification).…”
Section: Introductionmentioning
confidence: 99%